Reflections on the trends of suicide in Sri Lanka, 1997-2022: The need for continued vigilance. - Piumee Bandara; Prabath Wickrama; Sambasivamoorthy Sivayokan; Duleeka Knipe; Thilini Rajapakse (Public Library of Science (PLoS), 2024)
Despite reductions in suicide rates in Sri Lanka during the past decades, largely by introduction of national bans on highly hazardous pesticides, the country continues to record a higher than global average rate of suicide. With the changing availability of methods of suicide over time, we aimed to examine the age-standardized suicide rates in Sri Lanka by sex, age, and method between 1997 to 2022 using national police suicide data to identify trends. The rate of suicide in Sri Lanka in 2022 was 27/100,000 and 5/100,000, in males and females respectively, with an overall suicide rate of 15/100,000 population. When considering the previous decades, the overall rate of suicide has declined from 1997 until about 2015, in both sexes, driven by a drop in the numbers of suicides due to pesticide ingestion. In females the overall rates of suicide plateaued around 2015, but in males there has been an upward trend in overall suicide that started in 2016, mostly due to an increase in rates of hanging. Since 2016 rates of suicide by hanging have increased among older males, and young females (17-25 years). Whilst the current suicide rate in Sri Lanka is substantially lower than it was during the 1990s, the upward trend in hanging seen in the last few years, particularly among older men and young women, is of concern. Ongoing monitoring of suicide rates should be a priority during the next few years, to detect and respond to changes as soon as possible. There is an urgent need to address current risk factors for suicide in Sri Lanka, such as significant financial insecurity, unemployment, depression, alcohol misuse, and domestic violence, and to minimize media glamourization of hanging by suicide.